A modeling framework and analysis of challenges faced by the Indian petroleum supply chain. (15th January 2022) - Kumar, Sourabh; Barua, Mukesh Kumar
Abstract: This paper aims to determine the petroleum industry's supply chain challenges and develop Total Interpretive Structural Models (TISM) of the challenges faced by the companies and the consumers' perspective. From the companies' perspective, nine supply chain challenges were identified through rigorous literature review and experts' opinions. From the consumers' perspective, five challenges variables were identified by the literature and the north Indian retail consumers. A novel modeling technique, TISM methodology, describes the leading and lagging variables, which helped them convert the unstructured model to a well-articulated model. The MICMAC analysis is also performed to classify the contributory variables into different categories on the basis of their driving and dependence power. The study reveals that government policies, adverse weather conditions, and environmental regulation are the most influencing challenges, and resource availability is the least influencing by companies' perspectives. The quality and the price of products are the most influencing challenges, and social welfare is the least influencing by consumers' perspectives. This study uses the Indian petroleum industry to describe the proposed method's applicability. This research intended to guide the practitioners, policymakers, and academicians to emphasize their effort towards effective supply chain management in the petroleum industry. Highlights: Petroleum supply chain (PSC) is a series of activities. Various challenges occur in upstream, midstream, and downstream of industry. Total Interpretive Structural Modeling is proposed in the study. MICMAC analysis is performed to classify the contributory challenges variables. Results reveal environmental regulations are influencing supply chain challenges.